Molecular Imaging of Prostate Cancer - Wibmer, Andreas G. (Radiographics, 2016)
Prostate cancer is the most common noncutaneous malignancy among men in the Western world. The natural history and clinical course of prostate cancer are markedly diverse, ranging from small indolent intraprostatic lesions to highly aggressive disseminated disease. An understanding of this biologic heterogeneity is considered a necessary requisite in the quest for the adoption of precise and personalized management strategies. Molecular imaging offers the potential for noninvasive assessment of the biologic interactions underpinning prostate carcinogenesis. Currently, numerous molecular imaging probes are in clinical use or undergoing preclinical or clinical evaluation. These probes can be divided into those that image increased cell metabolism, those that target prostate cancer–specific membrane proteins and receptor molecules, and those that bind to the bone matrix adjacent to metastases to bone. The increased metabolism and vascular changes in prostate cancer cells can be evaluated with radiolabeled analogs of choline, acetate, glucose, amino acids, and nucleotides. The androgen receptor, prostate-specific membrane antigen, and gastrin-releasing peptide receptor (ie, bombesin) are overexpressed in prostate cancer and can be targeted by specific radiolabeled imaging probes. Because metastatic prostate cancer cells induce osteoblastic signaling pathways of adjacent bone tissue, bone-seeking radiotracers are sensitive tools for the detection of metastases to bone. Knowledge about the underlying biologic processes responsible for the phenotypes associated with the different stages of prostate cancer allows an appropriate choice of methods and helps avoid pitfalls. (©)RSNA, 2015